A novel approach for 3D discrete element modelling the progressive delamination in unidirectional CFRP composites. (January 2023) - Wan, Lei; Sheng, Yong; McCarthy, Edward D.; Yang, Dongmin
Abstract: This study proposed a novel approach based on the 3D discrete element method (DEM) to simulate the progressive delamination in unidirectional carbon fibre reinforced polymer (CFRP) composite laminates. A hexagonal packing strategy was used for modelling 0 ∘ representative plies, the interface between different plies was modelled with one bond and seven bonds following the conservation of energy principle and a power law. The number of representative layers and the stiffness of bonds within these layers were calibrated with a comparison of results obtained from finite element method and theoretical analysis. DEM simulations of delamination with both interface models were conducted on unidirectional composites for double cantilever beam (DCB), end-loaded split (ELS) and fixed-ratio mixed-mode (FRMM) tests. It was found that the seven-bond interface model has a better agreement with experimental data in all three tests than the one-bond interface model by adopting the proposed seven-bond arrangement in terms of the progressive delamination process. The main advantages of the present interface model are its simplicity, robustness and computational efficiency when elastic bonds are used in the DEM models. Highlights: 3D discrete element model with packed particles for anisotropic composite laminae. A novel bond approach with discrete element method for progressive delamination. Energy conservation principle based bond properties for interlaminar interface. Mode-I, mode-II and mix-mode fracture are captured with progression failure.